2022
DOI: 10.1101/2022.12.23.521796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GDF15 Is Required for Cold-Induced Thermogenesis and Contributes to Improve Systemic Metabolic Health Following Loss of OPA1 in Brown Adipocytes

Abstract: Previously we showed that mice lacking the protein optic atrophy 1 (OPA1 BKO) in brown adipose tissue (BAT) have induction of the activating transcription factor 4 (ATF4), which promotes fibroblast growth factor 21 (FGF21) secretion as a batokine. FGF21 increases metabolic rates at baseline conditions but is dispensable for the resistance to diet-induced obesity (DIO) reported in OPA1 BKO mice [1]. To determine alternative mediators of this phenotype, we performed transcriptome analysis, which revealed increas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We next considered whether DELE1 may be responsible for physiologic stress responses downstream of OMA1. We focused on cold stress in the heat-producing BAT, as cold stress has been shown to activate OMA1 and, in separate reports, cold stress has been reported to activate the ISR (Quirós et al , 2012; Jena et al , 2023; Flicker et al , 2019; Levy et al , 2023). Given OMA1 can be activated by mitochondrial uncouplers (Ehses et al , 2009; Head et al , 2009), activation of OMA1 in this setting is likely due to the fatty acid driven uncoupled mitochondrial respiration that produces heat (Nicholls, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…We next considered whether DELE1 may be responsible for physiologic stress responses downstream of OMA1. We focused on cold stress in the heat-producing BAT, as cold stress has been shown to activate OMA1 and, in separate reports, cold stress has been reported to activate the ISR (Quirós et al , 2012; Jena et al , 2023; Flicker et al , 2019; Levy et al , 2023). Given OMA1 can be activated by mitochondrial uncouplers (Ehses et al , 2009; Head et al , 2009), activation of OMA1 in this setting is likely due to the fatty acid driven uncoupled mitochondrial respiration that produces heat (Nicholls, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This anorexic effect is effectively abolished by blocking with a monoclonal antibody directed against GDF-15 and by GDF-15 or GFRAL knockout (KO) [66,102]. Recent studies have suggested that GDF-15 effect on body weight may be also associated with increased energy expenditure and thermogenesis [104]. Recently, Feng Lu et al found that GDF-15/GFRAL binding is an important determinant of the efficacy of ketogenic diet-induced weight loss.…”
Section: Conditionmentioning
confidence: 99%